Penerapan Augmented Reality pada WebGIS Zona Penangkapan Ikan Tongkol di Pulau Panjang - Vera Anggraini; Ramzan Pradana Maulsyid; Lukman Handyanto; Nuril Khairiyah; Haruni Najla Azizah; Bagus Firmansyah; Najwa Nur Hafazah (Universitas Methodist Indonesia, 2025)
Mackerel Tuna (Euthynnus Affinis) is a commodity with a high production rate in Banten Bay. Panjang island, which is geographically located in the waters of Banten Bay, is a potential area for supporting sustainable Tuna production. Market demand for this fish continues to grow, yet the lack of precise fishing zone data hampers resource optimization. The WebGIS system was developed to provide potential information on fishing zones for tuna around Panjang Island. Oceanographic data such as sea surface temperature and chlorophyll-a concentration were utilized to predict high-probability areas. This system features GPS-based augmented reality to guide fishers in real time to their targeted locations. Interactive and accurate information presentation facilitates decision-making for fishers. The implementation of this technology enhances fisher productivity while promoting sustainable fishery management. The potential of WebGIS technology offers significant opportunities for advancing Indonesia’s modern fishery sector, particularly for the coastal communities of Panjang Island.